2009
DOI: 10.1587/transinf.e92.d.1683
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Pressure and Tilt Input Techniques for Cursor Control

Abstract: SUMMARYThree experiments were conducted in this study to investigate the human ability to control pen pressure and pen tilt input, by coupling this control with cursor position, angle and scale. Comparisons between pen pressure input and pen tilt input have been made in the three experiments. Experimental results show that decreasing pressure input resulted in very poor performance and was not a good input technique for any of the three experiments. In "Experiment 1-Coupling to Cursor Position", the tilt input… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Tian and colleagues [32,33] showed that using pen tilt information could improve the stimulus-response compatibility and their "Tilt Cursor" utilized pen tilt to extend selection capability. Futhermore, Zhou and Ren [36] showed that tilt input performed relatively better than pressure input for cursor control. Bridson [4] used both translation and tilt of a pen to control viewpoint in a 3D scene, treating the pen as a handle attached to a selected point on the surface.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian and colleagues [32,33] showed that using pen tilt information could improve the stimulus-response compatibility and their "Tilt Cursor" utilized pen tilt to extend selection capability. Futhermore, Zhou and Ren [36] showed that tilt input performed relatively better than pressure input for cursor control. Bridson [4] used both translation and tilt of a pen to control viewpoint in a 3D scene, treating the pen as a handle attached to a selected point on the surface.…”
Section: Related Workmentioning
confidence: 99%
“…According to the aforementioned previous works, current pen-tilt-based interaction techniques can be classified into two types: (1) Tilt acquiring: users adjust the pen to a designate tilt angle either before or after placing the pen tip on the surface (e.g., using pen tilt to control the cursor [36] or to choose a pen mode once the pen tip contacts the tablet), and (2) Tilt pointing: users tilt the pen from one angle to another only after the pen tip is in contract with the surface (e.g., "tilt menu" [33], controlling a virtual human figure [21], 3D navigation [4,31]). Based on the study results, we discuss the implications for designing pen-tilt-based user interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al conducted a comparison study between the performances of pressure and tilt input when coupled to cursor position, angle, and scale [64]. For their first study, they mapped pressure and tilt control to control the position of a cursor that moved in a linear direction.…”
Section: Pressurementioning
confidence: 99%
“…Ramos et al found that humans can only distinguish up to 6 levels of pressure [45]. Research has also found that it was difficult for users to perform tasks that required a decrease in pressure level as it compromised completion time or accuracy [64]. Therefore, within our second study we included a task that focused on measuring the performance of changing (increasing and decreasing) bend and pressure input during linear movement.…”
Section: Pressurementioning
confidence: 99%
See 1 more Smart Citation